EFFECT OF SERVICE QUALITY AND SERVICESCAPE ON HOTEL CUSTOMER SATISFACTION IN SOLO - Muhammad Hasan Ma'ruf; Abdullah Zailani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research is an explanatory research type which aims to prove the hypothesis regarding the relationship of servicescape and service quality to customer loyalty through customer satisfaction. The research place is in the Hotel in Solo. Respondents in this study are repeater guast in one month period. The sampling technique uses non probability sampling, namely quota sampling. The number of samples obtained was 160 respondents. The findings of this study, namely servicescape, have no significant effect on customer satisfaction. Service quality has a significant effect on customer satisfaction. Keyword: servicescape, service quality, customer satisfication